A mistificação da accountability: processos ideológicos na realidade efetiva do mecanismo na educação - Menezes, Hermeson Claudio Mendonça (2023)
By acknowledging the ideological dispute in relation to the concept of accountability 3 a social technology of manipulation, of technocratic interventions, in favor of the reproduction of the status quo in the twentieth and twenty-first centuries 3 this thesis analyzes accountability, in particular, accountability in the educational field and its progressive process of mystification. Furthermore, it argues that this process converts accountability into an ideological mechanism that invigorates productivism 3 utilitarian densification 3 in the managerial era, contributing to make opaque or to mask the logic of inequality in the social metabolism of capital. Regarding accountability, linked to the very potential of a new managerial and governance institutional design in the neoliberal order, the following research problem is highlighted: How is the ideological mystification of educational accountability processed (increased and propagated)? As a result of this problem and in the face of the instrumentalization of accountability, in the society of phantasmagoria with its dynamics of power and control, it adds some questions, such as: In its historical development, how is the constitution of the content and form of accountability articulated? What is the raison d'être of educational accountability and accountability? In the managerial age, what quid pro quo contributes (and how?) to the mystification of accountability, producing the idea of an axiological neutrality? Exploring the characteristics of a socioeconomic project, with reverberations in the most diverse fields, the research is guided by the theory of dialectical materialist knowledge, which implied considering as a guiding methodological basis, the bibliographic research and the Marxian-Marxist categories 3 as essence and appearance, in scientific practice. By resorting to the literature on accountability, mostly centered on foucauldian, bourdieusian, postmodern theories and/or critical theory, there was a movement of confrontation, incorporation, rejection and supersumption of these currents of scientific knowledge. In the interweaving that involves accountability praxis, the study resorted, as an investigative contribution, to two other methodologies of a more episodic and/or indirect nature: documentary research and semi-structured interviews, with teachers and managers of outstanding schools (high performance), contemplated in the School with Excellence in Performance Award 2020, in the municipality of Fortaleza/Ceará. It also highlights the use of content analysis techniques, duly adjusted to marxian epistemology. In this work, by demystifying accountability 3 unveiling it as an organic ideology, a spectacle of market engineering in educational policy 3 the research concluded that mystified accountability is a deus ex machina – a mechanism of social control and power relations, whose substantialization If it takes place in interrelation and in interaction with the active mystification of the term, it occurs: through its terminological and conceptual reification; in the face of intransparent transparency; by its conceptualization, always expansive; by the dispute between its scholars; by virtue of organizational anthropomorphization; due to the ideology of scientific neutrality. Finally, in nebulous times, the thesis is a scientific text that challenges the hegemony of the barbarism of capital, contributing to demystify accountability, thus arming individuals in the struggle against the forces that reproduce exploitation and social inequality.